Maternal blood and amnionic oxytocin receptor gene expression and serum oxytocin levels in preterm birth: a case-control study - Kumari Anukriti; Kiran Guleria; Vipin Tyagi; Amita Suneja; B D Banerjee (Clinical and Experimental Obstetrics & Gynecology)
Purpose of investigation: The oxytocin (OXT)-oxytocin receptor (OXTR) system provides a promising candidate gene for studies of genetic contributions to prematurity. The author studies the quantification and comparison of oxytocin receptor (OXTR) gene expression and serum OXT levels in the blood and amnion of women delivering preterm and evaluation of the correlation between OXTR gene expression in blood and amnion with serum OXT levels in them. Material and methods: Seventy pregnant women in spontaneous labor delivering vaginally preterm i.e., < 37 weeks and an equal number of matched controls delivering spontaneously at term (37–42 weeks) were recruited. Maternal serum OXT levels were quantified by ELISA collected in the active stage of labor i.e., 4 cm cervical dilatation. Gene expression studies in the maternal blood and amnion were done by using real-time quantitative polymerase chain reaction (RT-qPCR). Results: The mean serum OXT level in preterm labor (PTL) was 48.56 ± 6.97 pg/mL; significantly higher than in controls (43.00 ± 3.96 pg/mL), P < 0.001. OXTR gene expression in maternal blood (2.5 times) as well as in amnion (3.5 times) was significantly higher in PTL. A significant positive correlation was observed between serum OXT levels and OXTR gene expression in amnion (r = -0.190, P = 0.025). Conclusions: The serum OXT levels and OXTR gene expression in amnion surge significantly in the active phase of PTL. Thus, amnion probably links OXT-PTGs (prostaglandins) autocrine paracrine circuit to facilitate PTL. Future studies are needed to devise better OXTR receptor antagonists preferably acting on amnionic OXTRs to prevent inflammatory pathways leading to PTL.